Exploring Intuitive Eating - Jennifer Campestrini; Amber Fritsche; Kelsi Garcia; Kaitlyn Grange; Kaylan Hebert; Anastasia Narizhnaya; Diannette Osorio Rexach; Rebecca Preece; Wendy J. Dahl (EDIS, 2022)
Intuitive eating is an eating framework created by two dietitians integrating instinct, emotion, and rational thought. Through ten principles, intuitive eating can help individuals become more in tune with the physical sensations of their bodies and adequately meet their biological and physiological needs. Additionally, intuitive eating helps to remove obstacles such as food rules and thought patterns instilled by diet culture. This new 8-page publication of the UF/IFAS Food Science and Human Nutrition Department explains the ten principles of intuitive eating in detail to help people searching for peace with food find practices that honor their physical and mental health. Written by Jennifer Campestrini, Amber Fritsche, Kelsi Garcia, Kaitlyn Grange, Kaylan Hebert, Anastasia Narizhnaya, Diannette Osorio Rexach, Rebecca Preece, and Wendy J. Dahl. https://edis.ifas.ufl.edu/fs443